Using computer software for energy saving determination in complex business processes – a case study of KGHM Polska Miedź S.A. - Sangórski, Mariusz; Wierzbic, Arkadiusz (Wykorzystanie oprogramowania komputerowego w celu określenia oszczędności energii w złożonych procesach biznesowych na przykładzie KGHM Polska Miedź SA, 2020)
The improvement of energy efficiency, which is the desired effect of pro-efficiency measures, is defined by determining the amount of energy savings as the impact of the effectively realised actions. Properly defined energy savings are the essential management information that, correctly used, can increase the value of the company as the knowledge about the effects of the decisions made. The proper definition of saving requires understanding of what it is because, without it, there is no chance for its correct determination, which makes the whole work worthless. The article aims to present the method used in KGHM Polska Miedź S.A. of properly implementing energy savings and the computer software used for this purpose. The method is based on the statistical modelling of energy use supported by a tool initially used for statistical process control. The described method applies not only to individual pro-efficiency activities or simple technological processes, but also to complex business processes, and the software is easy to use and in the described version, free of charge. The implementation of the described solution enables obtaining high-quality management information quickly and at a moderate cost
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 4 (58), s. 127-141
Keywords: informatyka ekonomiczna